Perbedaan Hasil Belajar Matematika Peserta Didik yang diajar dengan Strategi Pembelajaran Aktif Tipe The Power of Two dan Tipe The Learning Cell - Susanto, Andi; Sumiarti, Sumiarti (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The aim of this study is to determine differences of learning outcomes among mathematics learners who were taught by using the strategy of learning the type of power two and the learning Cell strategy at class VII of Junior High School (SMPN) 31 Padang. The Average result of the students those who were taught by The Power of Two was 74,00 and 73,78 for The Learning Cell. The Hypothesis testing obtained 0,803 for the t count and = 1,645 for the T-table. This indicate that there is a low significance difference on the result mathematics taught by using active strategy The Power of Two and Learning Cell.